2005
DOI: 10.1007/s00383-005-1408-7
|View full text |Cite
|
Sign up to set email alerts
|

Associated anomalies in children with congenital solitary functioning kidney

Abstract: Congenital solitary functioning kidney (CSFK) is a relatively common renal malformation and in children is frequently complicated by anomalies of the ipsilateral genital organs and occasionally by anomalies of other organs. The aim of this study was to determine the incidence of associated urological, cardiac, gastrointestinal, hematological, neurological, skeletal, and other congenital malformations in children with CSFK. We retrospectively reviewed 87 consecutive cases of CSFK diagnosed at our hospital betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 18 publications
1
23
0
2
Order By: Relevance
“…Thus assessment of the relative importance of a reduced nephron endowment per se in the onset of adult disease is extremely difficult. In human patients with unilateral renal agenesis, in whom nephron endowment is reduced from birth, the incidence of renal insufficiency and proteinuria is common (2,61), and, in many cases, infants with one kidney also have contralateral renal abnormalities (18,35,62), the most common of which may further contribute to renal problems. Children with unilateral renal agenesis often develop elevated arterial pressure (73,95), although it is difficult to know whether this is directly due to a reduced nephron endowment.…”
Section: Assessing the Importance Of A Reduced Nephron Endowmentmentioning
confidence: 99%
“…Thus assessment of the relative importance of a reduced nephron endowment per se in the onset of adult disease is extremely difficult. In human patients with unilateral renal agenesis, in whom nephron endowment is reduced from birth, the incidence of renal insufficiency and proteinuria is common (2,61), and, in many cases, infants with one kidney also have contralateral renal abnormalities (18,35,62), the most common of which may further contribute to renal problems. Children with unilateral renal agenesis often develop elevated arterial pressure (73,95), although it is difficult to know whether this is directly due to a reduced nephron endowment.…”
Section: Assessing the Importance Of A Reduced Nephron Endowmentmentioning
confidence: 99%
“…Konjenital böbrek anomalisi olan çocuklarda %10-50 oranında ürogenital sistem ve diğer sistemlere ait anormalikler eşlik edebilir (6,19,22) . Tek taraflı renal agenezi ve hipoplazi hastalarından oluşan bu çalışmada, 15 (%30) hastada ürogenital sistem anomalisi saptanırken, 7 (%28) hastada diğer sistemlere ait anomali mevcuttu.…”
Section: Discussionunclassified
“…Offspring and other relatives of individuals with congenital solitary kidney have a significantly increased incidence of renal disease (agenesis, dysplasia, cystic dysplasia) (McPherson 2007). A retrospective study of renal injury markers in children with SFK demonstrated that nearly one-third of the patients had hypertension or albuminuria or used renoprotective medication at a young age (Kaneyama et al 2004;Dursun et al 2005). We therefore emphasize that clinical follow-up of all children with an SFK is needed.…”
Section: Solitary Functioning Kidney (Sfk)mentioning
confidence: 99%